Extreme coastal water levels with potential flooding risk at the low-lying Saint Louis historic city, Senegal (West Africa) - Cisse, Cheikh Omar Tidjani; Brempong, Emmanuel K.; Taveneau, Adélaïde; Almar, Rafael; Sy, Boubou Aldiouma; Angnuureng, Donatus Bapentire (Frontiers in Marine Science, 2022)
In a context of global warming characterized by a mean sea level rise and extreme meteorological events, the study of the causes for coastal flooding is essential to protect communities and ecosystems. Densely urbanized, and rather unprotected cities in developing countries such as the historic Saint Louis city in Senegal are particularly vulnerable to coastal flooding and sea hazards. From satellite-derived high resolution DEM and global ocean reanalyses, here we quantify the extreme coastal water level in order to identify the neighborhoods and places of particular socio-economical interest of Saint-Louis potentially vulnerable to flooding. The results reveal that the most severe levels have the potential to flood up to almost half of this low-lying river mouth plain. Social, economic and heritage stakes are exposed, and the artisanal fisherman district of Gueth Ndar, is particularly vulnerable to coastal flooding because of its low elevation and situation on the sand barrier. The co-occurrence of high tides and wave-induced runup contributes most to ECWL but they do not present a significant trend over the study period. The results show that over the period 1994-2015, potential flood risk increased by nearly one day per year, primarily due to sea level rise, sounding a warning signal to take countermeasures to protect communities and infrastructure.